Antiferroelectric lead zirconate ceramics with nanoparticle alumina additions - Puchmark C. (2014)
The effects of alumina nanoparticles on the properties of PbZrO3 ceramics were investigated. The samples were prepared by a simple conventional mixed oxide method involving calcination and sintering temperatures of 800 °C and 1200 °C, respectively. Single-phase lead zirconate was observed in X-ray powder diffraction patterns for all the samples. The relationship between the Al2O3 content, the dielectric properties and Knoop hardness were determined. The results indicate that the additive affects Curie temperatures and the shape of the Curie peak, implying a chemical reaction takes place with the matrix during high-temperature processing. Hardness values increase for additions up to 1 vol % Al2O3. © 2008 Trans Tech Publications, Switzerland.